Mesophilic anaerobic digestion of waste activated sludge in an intermittent mixing reactor: Effect of hydraulic retention time and organic loading rate. (15th July 2023) - Leite, Wanderli Rogério Moreira; Scandolara Magnus, Bruna; Moraes, Bárbara Albuquerque Branco de; Kato, Mario Takayuki; Florencio, Lourdinha; Costa, Rejane Helena Ribeiro da; Belli Filho, Paulo
Abstract: An anaerobic digester was operated at mesophilic temperature and with intermittent mixing conditions to treat waste activated sludge. The organic loading rate (OLR) was increased by decreasing the hydraulic retention time (HRT), and the effect on process performance, digestate characteristics and inactivation of pathogens was investigated. The removal efficiency of total volatile solids (TVS) was also measured by biogas formation. The HRT varied from 50 to 7 days, corresponding to OLR from 0.38 to 2.31 kgTVS.m −3 .d −1 . The acidity/alkalinity ratio remained within stable limits (lower than 0.6) at 50-, 25- and 17-day HRT; due to an imbalance between the production and consumption of volatile fatty acids, the ratio increased to 0.7 ± 0.2 at HRT of 9 days and 7 days. The highest TVS removal efficiencies were 16, 12 and 9%, which were obtained at 50-, 25- and 17 day-HRT, respectively. Intermittent mixing provided solids sedimentation greater than 30% for almost all HRT tested. The highest methane yields (0.10–0.05 m 3 .kgTVSfed −1 .d −1 ) were obtained when the reactor was operated at a higher HRT (50-17 days). At lower HRT, methanogenic reactions were likely limited. Zinc and copper were the main heavy metals found in the digestate, while the most probable number (MPN) of coliform bacteria remained below 10 6 MPN.g TVS −1 . Neither Salmonella nor viable Ascaris eggs were found in the digestate. In general, increasing the OLR by decreasing the HRT to 17 days under intermittent mixing conditions provided an attractive alternative to treat sewage sludge despite some limitations due to biogas and methane yields. Graphical abstract: Image 1 Highlights: Sludge was digested covarying HRT and organic loading rate under intermittent mixing. Yields were 0.10 and 0.06 m 3 CH4 .kg TVSfed −1 .d −1, at 50- and 25 day-HRT, respectively. The bottom sludge supported the biogas production up to 17 day-HRT. Biomass wash-out and limited methanogenesis occurred at HRT lower than 17 days. Lighty and non-viable Ancylostoma eggs were more abundant in the digestate.